The origin of dust polarization in molecular outflows - Reißl, Stefan; Klessen, Ralf S. (Astronomy and astrophysics, 2017)
Aims. Polarization measurements of dust grains aligned with the magnetic field direction are an established technique for tracing large-scale field structures. In this paper we present a case study to investigate the conditions that need to be met to detect a characteristic magnetic field substructure that is embedded in such a large-scale field. A helical magnetic field with a surrounding hourglass-shaped field is expected from theoretical predictions and self-consistent magnetohydrodynamical (MHD) simulations to be present in the specific case of protostellar outflows. Hence, such an outflow environment is the perfect environment for our study. Methods. We present synthetic polarization maps in the infrared and millimeter regime of simulations of protostellar outflows. The simulations were performed with the newly developed radiative transfer and polarization code POLARIS. The code is the first to include a self-consistent description of various alignment mechanisms such as the imperfect Davis-Greenstein (IDG) and the radiative torque (RAT) alignment. We investigated the effects of the grain size distribution, inclination, and applied alignment mechanism. Results. We find that the IDG mechanism cannot produce any measurable polarization degree (≥1%), whereas the RAT alignment produced polarization degrees of a few percent. Furthermore, we developed a method for identifying the origin of the polarization. We show that the helical magnetic field in the outflow can only be observed close to the outflow axis and at its tip, whereas in the surrounding regions the hourglass field in the foreground dominates the polarization. Furthermore, the polarization degree in the outflow lobe is lower than in the surroundings, in agreement with observations. We also find that the orientation of the polarization vector flips around at about a few hundred micrometers because of the transition from dichroic extinction to thermal re-emission. In order to avoid ambiguities when interpreting polarization data, we therefore suggest to observe in the far-infrared and millimeter regime. The actual grain size distribution has only little effect on the emerging polarization maps. Finally, we show that it is possible to observe the polarized radiation emerging from protostellar outflows with ALMA.